http://www.tkea.com.ua/tkea/2008/6_2008/pdf/12.zip - Kavetskyy T. S.; Shpotyuk O. I.; Litovchenko P. G.; Tsmots V. M. (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature, 2008)
It is established radiation-induced decreasing in fragility of structural network takes place for γ-irradiated sample of Ge15,8As21S63,2 chalcogenide glass. It is concluded on the basis of the results obtained that radiation modification of chalcogenide glass leads to the rigidity of its matrix, and the vibrational (boson) contribution in the low-frequency spectral region is dominatе on the relaxation quasi-elastic scattering.